Vortex phase diagram in 12442-type RbCa2Fe4As4F2 single crystal revealed by magneto-transport and magnetization measurements. (5th October 2020) - Xing, Xiangzhuo; Yi, Xiaolei; Li, Meng; Meng, Yan; Mu, Gang; Ge, Jun-Yi; Shi, Zhixiang
Abstract: The recently discovered 12442-type ACa2 Fe4 As4 F2 (A = K, Rb, Cs) compounds are the only iron-based superconductors (IBSs) with double FeAs layers between neighboring insulating layers, analogous to the double CuO2 layers in some high- T c cuprates. Here, we report the study of vortex phase diagram of RbCa2 Fe4 As4 F2 single crystal via magneto-transport and magnetization measurements. The resistive transition under magnetic fields shows a foot-like kink at a characteristic temperature, T s, followed by a resistive tail in nearly zero resistivity region. Such behavior is ascribed to a vortex slush transition at T s, below which the vortex state has short-range vortex lattice correlation, and then a second-order transition into the vortex glass phase occurs with further decreasing temperature. Above T s, the Arrhenius plot of resistivity shows two linear regions that are separated by a crossover line T cr ( B ), which is associated with a crossover from collective to plastic pinning or different flux pinning behaviors resulted from different types of defect. In addition, the magnetic hysteresis loops reveal a second magnetization peak (SMP), which is shifted to lower fields with increasing temperature for T < 12 K. However, the SMP unexpectedly moves back to a higher field at T = 12 K, and then gradually turns into a shoulder or kink that moves to higher fields at high temperatures, such anomalous behavior has never been observed in IBSs. According to the magneto-transport and magnetization data, the vortex phase diagram of RbCa2 Fe4 As4 F2 is finally constructed. Details on the different vortex phase transitions and relevant physical scenarios are given and discussed.